Novel Data about Association of the Functionally Significant Polymorphisms of the MMP9 Gene with Exfoliation Glaucoma in the Caucasian Population of Central Russia - Starikova, Dina (Ophthalmic Res, 2021)
AIM: This study aimed to investigate the role of functionally significant polymorphisms of the MMP1, MMP3, and MMP9 genes in the development of exfoliation glaucoma (XFG) in the Caucasian population of Central Russia. METHODS: The study sample consisted of 724 participants, including 328 patients with XFG and 396 individuals in the control group. The participants were of Russian ethnicity (self-reported) born in Central Russia. The participants were genotyped at 8 functionally significant polymorphisms of the MMP genes (rs3918242, rs3918249, rs17576, rs3787268, rs2250889, rs17577 MMP9, rs679620 MMP3, and rs1799750 MMP1). The association analysis was performed using logistic regression. Two polymorphisms, which were associated with XFG, and 12 polymorphisms linked to them (r2 ≥ 0.8) were analyzed for their functional significance in silico. RESULTS: Allele C of rs3918249 MMP9 was associated with XFG according to the additive model (OR = 0.75, 95% CI: 0.56–0.93, pperm = 0.015), and allele G of the rs2250889 MMP9 locus was associated with XFG according to the additive (OR = 1.59, 95% CI: 1.10–2.29, pperm = 0.013) and dominant (OR = 1.68, 95% CI: 1.11–2.56, pperm = 0.016) models. Two XFG-associated loci of the MMP9 gene and 12 SNPs linked to them had a significant regulatory potential (they are located in the evolutionarily conserved regions, promoter and enhancer histone marks, the DNAase-hypersensitivity regions, a region binding to regulatory protein, and a region of regulatory motifs) and may influence the expression of 13 genes and alternative splicing of 4 genes in various tissues and organs related to the pathogenesis of XFG. CONCLUSION: Allele C rs3918249 MMP9 decreased risk for XFG (OR = 0.75), and allele G of the rs2250889 MMP9 locus increased risk for XFG (OR = 1.59–1.68) in the Caucasian population of Central Russia.